Pengaruh Penambahan Tepung Daun Kelor pada Ransum terhadap Kandungan Nutrisi dan Fisik Telur Itik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The aim of this study were to analyzed effect of adding Moringa leaf meal on feed in egg quality of duck.The livestock used were 27 ducks with 3 treatments and 3 replication and each replication there were 3ducks. P0 (feed + 0% Moringa), P1 (feed + 5% Moringa) and P2 (feed + 10% Moringa). Experimentaldesign used completely randomized design. Variables observed in this study were physical quality such asegg weight and yolk color score and chemical quality such as cholesterol and protein level. Observationwas carried out after 4 weeks of feed treatment. Significantly different result were seen in egg weightvariables (P0.05).